2018
DOI: 10.1063/1.5029980
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule electrophoresis of star polymers through nanopores: Simulations

Abstract: We study the translocation of charged star polymers through a solid-state nanopore using coarsegrained Langevin dynamics simulations, in the context of using nanopores as high-throughput devices to characterize polymers based on their architecture. The translocation is driven by an externally applied electric field. Our key observation is that translocation kinetics is highly sensitive to the functionality (number of arms) of the star polymer. The mean translocation time is found to vary non-monotonically with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 34 publications
8
45
0
Order By: Relevance
“…To isolate the effect of the polymer architecture, the total number of monomers, N = 1 + fm, was fixed at 121 in all cases. [26][27][28] Equation 3is integrated in time using the velocity Verlet algorithm with a time-step Δt = 0.005. At the start of each simulation, the terminal bead of one arm was placed just inside the nanopore, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To isolate the effect of the polymer architecture, the total number of monomers, N = 1 + fm, was fixed at 121 in all cases. [26][27][28] Equation 3is integrated in time using the velocity Verlet algorithm with a time-step Δt = 0.005. At the start of each simulation, the terminal bead of one arm was placed just inside the nanopore, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…At the start of each simulation, the terminal bead of one arm was placed just inside the nanopore, as shown in Figure 1. [26,27] With this bead fixed in position, the chain was allowed to equilibrate until the radius of gyration fluctuated about an equilibrium value. Subsequently, the bead originally placed inside the nanopore was released and the external force was turned on.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…H. H. Katkar and M. Muthukumar studied the translocation of charged star polymers of constant mass driven by an externally applied electric field by varying chain functionality. [59] Their main finding is that the translocation kinetics is strongly affected by the polymer functionality with a non-monotonic dependence of the translocation time with respect to functionality and the existence of a critical functionality for which the translocation is the fastest. The authors also reported that the translocation was found to be impossible for chains above a particular functionality when the nanopore radius was sufficiently small.…”
Section: Introductionmentioning
confidence: 99%